Splice system in extending the precast prestressed concrete beam span - Kamarol Zaki, Mohd. Nasir (2009)
This project focuses on the use of splicing precast concrete beams to extend their span length. Precast prestressed concrete beams are economical solutions for many bridges, due to various restrictions such as weight and hauling length they are rarely used for spans greater than 40 m. This project was initiated by collecting the information from internet and technical reports of some bridge projects that have used spliced beam system. The experimental work has been carried out on three beams of 2.5 m span with different location of splice loaded to fail. The type of splice beam system used consisted of precast pretensioned beam joint together by post-tensioned method. The experimental results show the development at shear failures inclined the depth opposed with initial prediction to fail in flexure. Both spliced beam has achieved the ultimate load capacity. On the other hand, the actual load capacity for controlled beam was twice times higher than calculated. From this research, base on ultimate load failure, the spliced system applied for double spliced beam has succeeded to perform as calculated nominal beam. However, since the actual controlled beam perform better, and the splice beam fail unexpectedly in shear, the future research should focusing on the materials, location and type of splice section to improve the present research.